ANALISIS VALIDITAS RELIABILITAS DAN INDEKS KESUKARAN PADA BUTIR SOAL MATERI BARISAN DAN DERET BERDASARKAN TAKSONOMI BLOOM REVISI - Fentiawati Trysna Dinata; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze and categorize in accordance with the validity, reliability and difficulty index of each item of barisan and series material in high school students class XII IPA 4 in one of the public schools in Cimahi city with a sample used by 28 people. The indicators used to analyze the problem are based on a revised Bloom Taxonomy that contains the cognitive domain levels C2 (understanding), C3 (Applying), C4 (Analyzing), C5 (Evaluating) and C6 (Creating). This type of research is qualitative descriptive research. The analysis is done by giving a written test in the form of a description question that amounts to 10 questions, then analyzing the test results that have been done. The method used is content analysis with the help of Microsoft Office Excel. The results of the analysis showed that out of the 10 question items tested there are 6 questions that can be used with the average result of validity and reliability in the moderate category as well as a difficulty index that shows the categories of easy, medium and difficult questions.